2020
DOI: 10.3390/su12072743
|View full text |Cite
|
Sign up to set email alerts
|

What if Employees Brought Their Life to Work? The Relation of Life Satisfaction and Work Engagement

Abstract: Previous research on work engagement has sought to understand the drivers, as well as the consequences, of engaging people at work. The drivers of engagement have been found mainly within the work domain. However, working life is not detached from personal life, which has been demonstrated by research on work-life balance. The goal of this research is to understand the relation between life satisfaction and work engagement. Data were collected from a sample of 571 employees from major Portuguese companies usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…Career success demands an individual employee to devote and manage their work-life in a more self-directed manner (Lee et al 2016;Mas-Machuca et al 2016). It is vital to examine the social contexts in measuring career success factors related to employee work-life balance (Ferreira et al 2020). Similarly, the associations between career commitment, career success, and work-life balance are likely to have different meanings in emerging Asia economies.…”
Section: Introductionmentioning
confidence: 99%
“…Career success demands an individual employee to devote and manage their work-life in a more self-directed manner (Lee et al 2016;Mas-Machuca et al 2016). It is vital to examine the social contexts in measuring career success factors related to employee work-life balance (Ferreira et al 2020). Similarly, the associations between career commitment, career success, and work-life balance are likely to have different meanings in emerging Asia economies.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, for the purposes of state policy aimed at achieving a balance between the formation and development of human capital, attention should be paid to the concept of sustainable development of human capital. This concept is appropriate for managing it at both the micro and macro levels [2]. The concept of sustainable development of human capital emphasizes a fair attitude towards its bearer, the need to take care of its development, health and well-being, supports environmentally friendly organizational practices, and is focused on work-life balance [20].…”
Section: Fig 2 Ranking Of Countries By the Hci On The World Mapmentioning
confidence: 99%
“…At the same time, within the framework of achieving sustainable development, the importance of ensuring a high quality of life for current and future generations is emphasized. Thus, the transition to sustainable development poses serious challenges for all components of the socio-economic structure of society, and a person here appears as a key subject of sustainable development [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, De Cuyper et al [ 32 ] identified a significant relationship between life satisfaction and work engagement. Subsequently, Ferreira et al [ 33 ] underlined that work engagement can be related to other aspects of workers’ lives besides their job and organizational roles, because working life is a part of the wider personal life, as demonstrated by studies on work-life balance.…”
Section: Introductionmentioning
confidence: 99%